2000
DOI: 10.1207/s1532694204connor
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Prenatal Alcohol Damage on Executive Function

Abstract: Patients with Fetal Alcohol Syndrome (FAS) and Fetal Alcohol Effects (FAE) often have difficulty functioning appropriately in everyday life and seem to employ poor problem-solving strategies. Tests of executive function are relevant for quantifying the functional deficits and underlying real-life problems associated with prenatal alcohol exposure. This study considers two pathways for the effects of prenatal alcohol on executive function: a direct effect and an indirect effect through prenatal alcohol's effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
186
0
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(208 citation statements)
references
References 35 publications
13
186
0
8
Order By: Relevance
“…In comparison to typically developing controls, our alcohol-exposed group displayed deficits on all tasks except for TMT-A, although the group difference on category fluency was only marginally significant ( p 5 .059). These deficits are consistent with previous reports of deficits on the WCST (Carmichael Olson et al, 1998;Connor et al, 2000;Kodituwakku et al, 1995), verbal fluency (Kodituwakku et al, 1995;Schonfeld et al, 2001), and trail making in this population. In addition, the ALC group displayed significantly poorer performance on letter fluency than category fluency, which is consistent with previous findings suggesting that letter fluency is better than category fluency at discriminating children with FASD from controls (Kodituwakku et al, 1995;.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In comparison to typically developing controls, our alcohol-exposed group displayed deficits on all tasks except for TMT-A, although the group difference on category fluency was only marginally significant ( p 5 .059). These deficits are consistent with previous reports of deficits on the WCST (Carmichael Olson et al, 1998;Connor et al, 2000;Kodituwakku et al, 1995), verbal fluency (Kodituwakku et al, 1995;Schonfeld et al, 2001), and trail making in this population. In addition, the ALC group displayed significantly poorer performance on letter fluency than category fluency, which is consistent with previous findings suggesting that letter fluency is better than category fluency at discriminating children with FASD from controls (Kodituwakku et al, 1995;.…”
Section: Discussionsupporting
confidence: 93%
“…Although the groups displayed similar impairment, WCST performance of the ALC group was significantly better than predicted by IQ, whereas in the ADHD group, the opposite was true. Other studies in alcohol-exposed children and adults have reported EF deficits that remain after IQ is controlled or that are worse than predicted based on IQ deficits (Carmichael Olson et al, 1998;Connor et al, 2000;Kerns et al, 1997;Schonfeld et al, 2001). Although the reason for these conflicting results is unclear, it may be due to task or sample differences.…”
Section: Discussionmentioning
confidence: 96%
“…However, more than half of the associated characteristics are linked to the socio-economic environments in which these mothers live and work 10,25,26,27,28 . The information gathered thus far provides limited understanding of how culture, economy and politics perpetuate marginalisation amongst women who drink during pregnancy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The criteria for purposeful sampling were drawn from literature describing the traits of mothers who are at risk for having children with FAS 20,25,26,27 . Accounting for elements of balance and variety in age, stage of pregnancy and key socio-economic factors was of greater importance than a larger sample.…”
Section: Participant Samplingmentioning
confidence: 99%
“…The first are behavioral/cognitive studies comparing the behavioral performance of exposed to nonexposed individuals on various neuropsychological tasks with the goal of understanding the neurocognitive phenotype associated with exposure. While many differences in functioning, including attention (Coles et al 1997;Nanson and Hiscock 1990), memory (Mattson et al 1996), verbal ability (Schonfeld et al 2001), and executive function (Connor et al 2000), have been identified as impaired in alcohol-exposed individuals, inconsistencies remain, however, between studies and across developmental stages. Specific behavioral markers (if there are any) have not been delineated as yet.…”
Section: Introductionmentioning
confidence: 99%